Neuroscience and education: Issues and opportunities : a commentary by the teaching and learning research programme - Howard-Jones, Paul (Institute of Education, 2007)
In a recent survey of teachers, almost 90 per cent thought that a knowledge of the brain was important, or very important, in the design of educational programmes1. Indeed, for at least two decades, educational programmes claiming to be ‘brain-based’ have been flourishing in the UK. Unfortunately, these programmes have usually been produced without the involvement of neuroscientific expertise, are rarely evaluated in their effectiveness and are often unscientific in their approach. Perhaps this is unsurprising since, although the central role of the brain in learning may appear self-evident, formal dialogue between neuroscience and education is a relatively new phenomenon.
Keywords: neurosciences; utilisation des recherches